Survival analysis of patients with spinal chordomas - Sun, Huihui; Liu, Bing; Cui, Jiaqu; Zhou, Zhao-Ming (Neurosurgical review, 2019)
This study was aimed to analyze the survival of patients with spinal chordomas. Patients’ data in the Surveillance, Epidemiology, and End Results (SEER) database were retrieved and analyzed statistically. There were 765 patients with spinal chordomas between 1974 and 2013. The overall survival did not improve significantly over decades for patients receiving surgery and radiotherapy (SR) (P = 0.221). There were significant differences in overall survival among subgroups of patients receiving surgery (S), radiotherapy (R), and neither S nor R (NSR) (P = 0.031, 0.037, and 0.031, respectively). Cancer-specific survival did not change significantly among subgroups of patients receiving R (P = 0.411), while it increased steadily among subgroups of patients receiving S, SR, and NSR (P < 0.001, 0.001, and 0.049, respectively). In the multivariate Cox regression model, younger onset age (hazard ratio [HR] 1.052, P < 0.001), surgery (HR 0.291, P = 0.001), and tumor location of the sacrum (HR 0.401, P = 0.002) were associated with a better overall survival. Similarly, younger onset age (HR 1.036, P = 0.029), surgery (HR 0.221, P = 0.009), and tumor location of the sacrum (HR 0.287, P = 0.002) were also associated with a higher cancer-specific survival. The changes in overall and cancer-specific survival over time differ among different treatment groups. Younger onset age, surgical strategy, and tumor location of the sacrum may be correlated with a higher overall and cancer-specific survival.
Gesehen am 01.08.2019
Published online: 7 May 2018